(untitled) - DELVIA FIRDIANTI, FIQIH (RETAIN : Journal of Research in English Language Teaching, 2013)
This study is conducted to describe the relevance of the reading materials to the 2006 English Standard Competence and to describe the relevance of the reading materials to the criteria of good reading material adapted from Depdiknas and BSNP. This study was designed as a documentary analysis in the form of descriptive qualitative research without any statistical calculation. The result of this analysis showed that all of the reading materials presented in the textbook are relevant to the 2006 English standard competence and the reading materials are fullfilled the criteria of the reading material adapted from Depdiknas and BSNP. The reading materials presented in the textbook are quite appropriate to be given to the students. It will be better if the teacher can be more creative to prepare the other materials from other sources. Also, they can add some contents or modify the activities presented in the textbook based on the students’ need or ability. Keywords: analysis, reading materials, textbook. Abstrak Penelitian ini dilakukan untuk menggambarkan relevansi bahan bacaan dengan Standar Kompetensi Bahasa Inggris tahun 2006 dan untuk menggambarkan relevansi bahan bacaan dengan kriteria bahan bacaan yang baik yang diadaptasi dari Depdiknas dan BSNP. Penelitian ini dirancang sebagai analisis dokumenter dalam bentuk penelitian deskriptif kualitatif tanpa perhitungan statistik. Hasil analisis ini menunjukkan bahwa semua bahan bacaan yang disajikan dalam buku teks yang relevan dengan kompetensi 2006 standar bahasa Inggris dan bahan bacaan yang memenuhi kriteria bahan bacaan diadaptasi dari Depdiknas dan BSNP. Bahan bacaan yang disajikan dalam buku teks ini termasuk sudah tepat untuk diberikan kepada para siswa. Akan lebih baik lagi jika guru bisa lebih berkreasi untuk mempersiapkan bahan-bahan lain dari sumber lain. Mereka juga dapat menambahkan beberapa isi atau memodifikasi kegiatan yang disajikan dalam buku teks berdasarkan atas kebutuhan atau kemampuan siswa. Kata kunci: analisis, bahan bacaan, buku teks.